HIV/AIDS in the fisheries sector in Africa - Gordon, Ann (Worldfish Center, 2005)
Poverty in Africa is still a largely rural phenomenon. Rural economic development is thus critical to poverty alleviation in Africa. Africa’s fisheries can be an engine of growth because there is robust local and international demand for fish products (both marine and freshwater) and under-exploited potential for fish farming. Fish products are also an important source of affordable animal protein and micronutrients for Africa’s poor. Yet fisheries livelihoods are severely threatened.